2019
DOI: 10.1016/j.eswa.2018.10.043
|View full text |Cite
|
Sign up to set email alerts
|

Prediction interval methodology based on fuzzy numbers and its extension to fuzzy systems and neural networks

Abstract: Prediction interval modelling has been proposed in the literature to characterize uncertain phenomena and provide useful information from a decision-making point of view. In most of the reported studies, assumptions about the data distribution are made and/or the models are trained at one step ahead, which can decrease the quality of the interval in terms of the information about the uncertainty modelled for a higher prediction horizon. In this paper, a new prediction interval modelling methodology based on fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 60 publications
0
40
0
1
Order By: Relevance
“…The ACO R algorithm keeps track of k best solutions in a matrix S k×n , called the Solution Archive (SA). Each single row in this archive is made of the vector of model parameters and the value of the corresponding objective function f ( s ) obtained after running the flow simulation 38 . The algorithm sorts the remaining models in the archive according to their determination value (Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…The ACO R algorithm keeps track of k best solutions in a matrix S k×n , called the Solution Archive (SA). Each single row in this archive is made of the vector of model parameters and the value of the corresponding objective function f ( s ) obtained after running the flow simulation 38 . The algorithm sorts the remaining models in the archive according to their determination value (Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…In [9], Takagi Sugeno (T-S) fuzzy models are utilised and by following the principles in [10] and upperlower prediction interval bounds -based on a given percentage value-are provided by utilising the covariance of data. Thereafter, a new prediction interval modelling methodology based on fuzzy numbers is proposed [11] which generate the size of prediction intervals based on a given percentage value. Fuzzy Set (FS) theory was introduced by Zadeh [12] and is applied to Fuzzy Logic Systems (FLSs) which are considered as explainable and robust systems for capturing and handling uncertainty in decision making applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, the accuracy of MVE based method greatly depends on whether the related prediction model can precisely estimate the mean value of the target. The study [22] reported an instance of NN-based construction of PIs incorporating fuzzy member. Considering that the modeling considerations in this case are specialized in the field of renewable energy, the method cannot be directly applied to gaseous system of steel industry.…”
Section: Introductionmentioning
confidence: 99%